(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Religious minorities and spiritual assistance. Reflections on the project “Atlas of religious or belief minority rights” in European Union The category of religious minority is particularly relevant within the European Union, where there is a common system for the protection of religious minorities and beliefs. This allows for an assessment of Member States’ promotional behaviour. Tools for measuring international human rights provisions are becoming increasingly widespread, even within religious studies. Against this backdrop, the research project Atlas of Religious or Belief Minority Rights opens up possibilities for the legal analysis of how religious minorities’ rights are respected and promoted, starting from international standards in this area. From a comparative perspective, the case of spiritual assistance in separate facilities is an interesting field of investigation into the behaviour of EU Member States. Analysis of the project results highlights the need to reform the regulation of spiritual assistance, particularly in countries with a historical religious majority, to take into account the changed religious landscape in Europe. Recognition of the legal status of old and new religious and belief minorities largely determines access to rights. SOMMARIO: 1. Introduzione. La categoria di minoranza religiosa entro il sistema delle fonti multilivello. La creazione di un sistema di tutela comune nello spazio Ue e la valutazione delle politiche degli Stati membri dell’Unione europea. - 2. Le minoranze religiose e di convinzione alla prova delle tecniche di misurazione del rispetto e promozione dei diritti umani. Il caso dell’Atlas of religious or belief minority rights. - 3. L’assistenza spirituale nelle structure separate. International standards e giurisprudenza europea nel sistema di valutazione dei comportamenti degli Stati membri. - 4. Il diritto all’assistenza spirituale negli Stati membri Ue: spunti per un’analisi comparata. - 5. Osservazioni conclusive. Verso una riforma condivisa dell’approccio alla tutela dei diritti delle minoranze di religione e convinzione.